Assessing the Role of Mortgage Finance in Addressing Housing Needs: A Comparative Analysis Between Jos and Kano - Gombwer, Nenrot Wuyokwe; Sani Inusa Milala (International Journal of Scientific Research and Innovative Studies, 2024)
This study investigates the impact of mortgage finance on addressing housing needs, comparing the effectiveness between Jos and Kano. The primary objective is to evaluate how mortgage financing contributes to housing development in these cities. Utilizing a quantitative research design, the study employed purposive sampling to gather data from Primary Mortgage Institutions (PMIs) and the Real Estate Developers Association of Nigeria (REDAN). Out of 40 distributed questionnaires, 37 were completed and returned14 from Jos and 23 from Kano. The analysis reveals notable differences in mortgage finance operations between the two cities. Jos is served by a single PMI and federal mortgage bank, with seven REDAN members, while Kano has two PMIs, ten REDAN members, and similar federal institutions. Loan data indicates that Jos had 1,898 applicants requesting a total of 3,180 million Naira in loans, with 1,179 loans approved and 3,650 million Naira disbursed over ten years. In contrast, Kano had 2,925 applicants with a total loan request of 4,160 million Naira, approving 1,558 loans and disbursing 3,515 million Naira. Despite Kano’s higher number of applicants, Jos had a higher total disbursement. Additionally, the annual budgets for housing development were significantly larger in Kano compared to Jos, reflecting Kano’s greater financial commitment. These findings highlight that while both cities are actively engaged in mortgage financing, Kano shows a higher volume of loan applications and substantial disbursements, whereas Jos demonstrates a higher proportion of loan disbursement relative to applications. The study emphasizes the need for tailored financial strategies to effectively meet regional housing demands and outlines key differences in financial practices and priorities between Jos and Kano. The study concludes that Kano’s larger budget and higher loan volumes contrast with Jos’s more effective loan disbursement, highlighting regional differences in mortgage finance strategies and housing development. Key words: Mortgage finance, housing development, Jos, Kano, loan disbursement. Received Date: July 06, 2024 Accepted Date: July 27, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/177 DOI: https://doi.org/10.5281/zenodo.13371189